Ganglioneuroma has a potential for lymph node metastasis, not impacting recurrence - Ozcelik, Ender Eren; Sahin, Ahmet Bilgehan; Karaman, Yagmur; Erkan Ozmarasali, Buket; Yalcinkaya, Ulviye; Cubukcu, Erdem; Deligonul, Adem; Evrensel, Turkkan (Frontiers in Oncology, 2026)
Ganglioneuromas are rare, benign tumors arising from neuroblastic cells in the autonomic sympathetic nervous system. While generally considered indolent, limited case reports suggest their potential for regional metastasis. This retrospective study analyzed the clinical, demographic, and pathological features of 25 adult patients diagnosed with ganglioneuroma at Bursa Uludag University, Faculty of Medicine, between April 2007 and November 2023. The cohort comprised 18 females (72%) and seven males (28%), with a median age of 42 years (range: 19–79). Tumors were most commonly located in the abdomen (64%), followed by the thoracic (24%) and head and neck regions (12%), with the adrenal gland being the primary site in 32% of cases. Symptoms were present in 56% of patients, including pain, vision loss, hypertension, and palpable masses, while the remaining were asymptomatic. Surgical resection was performed in 92% of cases, with a median tumor size of 7.5 cm (1.5–18 cm). Median follow-up time was 88.3(16.2 - 217.8) months. Regional lymph node metastases were identified in 8% of patients, but no distant metastases or recurrences were observed during follow-up. These findings, including the novel observation of regional metastases, contribute valuable insights to the limited literature on ganglioneuromas. Despite its benign nature, this study highlights the potential for lymph node metastasis. However, the relationship between lymph node metastasis and recurrence has not been documented. In this context, further research is essential to better understand the risk factors, tumorigenesis, and the optimal management strategies for this rare tumor.